2011
DOI: 10.1590/s1980-57642011dn05030008
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric symptoms as the main determinant of caregiver burden in Alzheimer's disease

Abstract: Caregiver burden is common in Alzheimer’s disease (AD), decreasing the quality of life among caregivers and patients. Projections of aging and aging-related diseases such as AD in developing countries justify additional data about this issue because people living in these countries have shown similarly high levels of caregiver strain as in the developed world.ObjectiveThe aim of this study was to analyze the association of AD caregivers’ burden with patients’ neuropsychiatric symptoms (NPS), cognitive status, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
7
0
2
Order By: Relevance
“…These results are consistent with those reported in previous studies analyzing the impact of NPS on caregiver burden and quality of life. Kochhann et al 22 studied this association and concluded that NPS in patients with AD are the main cause of caregiver distress and burden, and that this association becomes stronger as the severity of dementia increases.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with those reported in previous studies analyzing the impact of NPS on caregiver burden and quality of life. Kochhann et al 22 studied this association and concluded that NPS in patients with AD are the main cause of caregiver distress and burden, and that this association becomes stronger as the severity of dementia increases.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropsychiatric symptoms (NPS) are common in dementia, greatly impacting the quality of life and caregiver burden [ 1 3 ]. The underlying neuropathological mechanisms of NPS are not sufficiently comprehended, but have been linked to region-specific pathology of brain areas, such as the cingulate cortex and left frontal cortex [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…O papel de cuidador é visto, culturalmente, como uma função feminina (8)(9) , incutindo à mulher do núcleo familiar o papel de tutora quando um adulto dependente necessite de cuidados. No presente estudo, a média de idade pode ser considerada baixa (38,9 anos) se comparado a outros estudos que relatam que os cuidadores pertencem à faixa etária superior a 55 anos (10)(11)(12) .…”
Section: Discussionunclassified